Fixed-time sliding mode flight control with model-based switching functions of quadrotor unmanned aerial vehicles. (8th April 2022) - Fallaha, Charles; Kali, Yassine; Saad, Maarouf; Ghommam, Jawhar
This paper proposes the design of a new sliding mode controller of the attitude fast inner-loop of a drone quadrotor type system. The controller uses the novel model-based switching functions approach, which leads to important simplifications of the pitch, roll and yaw torques control inputs fed to the quadrotor. The model-based switching functions approach forces as well a complete chattering decoupling of these three torque inputs and enhances the robustness of the closed-loop system. The proposed approach is combined with the fixed-time sliding mode approach, and is experimentally implemented and successfully validated on a quadrotor system.